2000
DOI: 10.3171/jns.2000.93.supplement_3.0019
|View full text |Cite
|
Sign up to set email alerts
|

Gamma knife radiosurgery for pituitary adenomas

Abstract: Object. The purpose of this study was the analysis of a large series of patients treated with gamma knife radiosurgery for pituitary adenoma in a single institution. Methods. One hundred eight patients with pituitary adenomas were treated over the last 7 years. Seventy-four patients have been followed for more than 6 months and form the basis of this report. Conclusions. Twenty-three patients harbored nonfunctioning adenomas, and 56 harbored functioning adenomas. The mean margin dose was 22.5 Gy (nonfunctionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(52 citation statements)
references
References 4 publications
1
50
0
1
Order By: Relevance
“…Encouraged by these results, some Asian centers started to treat again patients primarily with radiosurgery. At median follow-up times of about 2 years, 40-100% of the patients achieve hormonal normalization [47,56,62,69,85,94]. Toxicity was very low in these series.…”
Section: Radiosurgerymentioning
confidence: 79%
“…Encouraged by these results, some Asian centers started to treat again patients primarily with radiosurgery. At median follow-up times of about 2 years, 40-100% of the patients achieve hormonal normalization [47,56,62,69,85,94]. Toxicity was very low in these series.…”
Section: Radiosurgerymentioning
confidence: 79%
“…These cases may be both clinically asymptomatic and selfresolving [3,33]. Patients with prior irradiation appear to be more susceptible to radiation-induced brain necrosis [4,[33][34]. With current technological advancements of radiotherapy techniques, it is expected that the significant reduction of radiation treatment fields will translate into brain necrosis being a rare occurrence.…”
Section: Other Adverse Eventsmentioning
confidence: 94%
“…The reported results of GK SRS for non-functioning adenomas of 584 patients in 14 studies are shown in Table 2 [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. Six studies reported actuarial PFS with a 5-year control rate in the region of 94% at a median follow up of 44 months and because of size restriction of SRS this usually refers to small residual tumours.…”
Section: Radiosurgery (Srs)mentioning
confidence: 96%